1998
DOI: 10.1146/annurev.publhealth.19.1.101
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Risk Factors and Female Breast Cancer

Abstract: The increasing incidence of breast cancer in the United States and the international variation in risk have led to speculation that environmental risk factors are an important cause of breast cancer. We review the epidemiologic evidence on the breast cancer risk associated with ambient environmental exposures experienced passively by the US population, and discuss the difficulties associated with measurement of specific exposures in environmental studies. We review geographic variation of breast cancer rates i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(39 citation statements)
references
References 107 publications
1
36
0
2
Order By: Relevance
“…To examine physicians' knowledge of other breast cancer prevention approaches, they were asked approximately 10 common risk factors, including: positive family history for breast cancer, for ovarian cancer, for breast and ovarian cancer; personal history of breast cancer, of ovarian cancer, of breast and ovarian cancer; increased age, late age at first pregnancy or nulliparity, early age at menarche, late age at menopause. [53][54][55][56][57][58] The number of correctly identified risk factors were summed to form a continuous measure.…”
Section: Methodsmentioning
confidence: 99%
“…To examine physicians' knowledge of other breast cancer prevention approaches, they were asked approximately 10 common risk factors, including: positive family history for breast cancer, for ovarian cancer, for breast and ovarian cancer; personal history of breast cancer, of ovarian cancer, of breast and ovarian cancer; increased age, late age at first pregnancy or nulliparity, early age at menarche, late age at menopause. [53][54][55][56][57][58] The number of correctly identified risk factors were summed to form a continuous measure.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to established risk factors, it has been hypothesized that environmental exposures may also contribute to breast cancer risk [1][2][3]. Potentially important in explaining observed differences in breast cancer rates over time and between countries are exposures related to industrialization.…”
Section: Introductionmentioning
confidence: 99%
“…Among contaminants found in fish are mercury (45), polychlorinated biphenyls (46), organochlorine residues, and other chemicals. These chemicals have high toxicity and carcinogenic potency, and a few epidemiological studies suggested that pesticides and some of these chemicals may be related to breast cancer risk (47,48).…”
Section: Discussionmentioning
confidence: 99%